Testing of Bacterial Resistance in Urine of UTI Patients to Levofloxacin and Ciprofloxacin Antibiotics in Makassar Prodia Clinic Laboratoryâ€ - Asmawiah Rame; Vector Stephen Dewangga (UNIVERSITAS SAM RATULANGI, 2022)
ABSTRACTUrinary tract infection (UTI) is a clinical condition due to the proliferation of microorganisms that cause inflammation in the urinary tract and cause bacteriuria. Bacterial resistance to antibiotics continues to change, so research is carried out on the level of resistance to certain antibiotics in order to facilitate the treatment of UTI. Urine culture examination includes culturing the suspect bacteria, identifying and testing the antibiotics ciprofloxacin and levofloxacin. This study uses a descriptive research design. The sample of this study was 27 samples taken from patients who had been diagnosed with UTI and underwent therapy from a doctor. The results of the study of bacteria causing UTI resistance to the antibiotic levofloxacin 41%, and to the antibiotic ciprofloxacin 44%. Streptococcus agalactiaeÂ bacteria were found to be antibiotic resistant to levofloxacin and ciprofloxacin 37.5%,Â Escherichia coli was found to be antibiotic resistant to levofloxacin and ciprofloxacin 50%, Staphylococcus aureus was to be antibiotic resistant to levofloxacin 0% and ciprofloxacin 25%, and to floxacin to the antibiotic floxacin 25%, to be antibiotic resistant to floxacin. Streptococcus pyeogenes was found to be 0% resistant to levofloxacin and ciprofloxacin antibiotics, and toÂ Klebsiella oxytocaÂ and Enterococcus faecalisÂ were found to be 100% resistant.